THE USAGE FACTORS OF CODE SWITCHING IN TEACHING INTERACTION OF ENGLISH CLASS - Aa Qona'atun (FKIP, Universitas Banten Jaya, 2018)
The objective of this research is to gain a deep understanding and to know the use of code-switching done by lecturers and students in interaction when learning process in English class. Sub focus in this study is to determine the factors behind the use of code switching used by both speakers and partners said that in this case the interaction between lecturers and students when learning process in English class. This research was conducted on campus of State Islamic University Faculty in second semester.This research is a qualitative research using ethnographic method. The researcher examines the factors behind the use of code switching in interaction when learning process in the classroom. The research procedure by collecting data, processing, analyzing, and then presenting data objectively about the phenomenon of code switching in the interaction of teaching in English class. The use of documents on the grounds that: for a stable source, useful as a proof, because of its scientific, non-reactive nature, and the result of document review will open up the opportunity to further expand the growth and development of knowledge of something investigated. (4) The data in the research are: words, phrases, and sentences from informants as mentioned above. Data collection techniques are: (1) Observation. The tool used to assist this observation is the tape recorder. (2) Interview. (3) Documentation. The result of the research shows that there are seven factors that have been found related to the use of code switching: (1) factor of language limitations, (2) habit factor, (3) factor explaining something, (4) reflex factor, (5) base factor (entertainment), (6) factors of concern, (7) factors influenced by good speech partners between lecturers with students or students with other students.